Analisis Kekuatan Material Komposit Serabut Kelapa Hasil Metode Press Hand Lay-up dengan Curring Oven pada Variabel Waktu - Bisma Faris Santoso; Fadhil Muhammad; Syarif Hidayat (INOVTEK - SERI MESIN, 2021)
This research contains about how much the increase in the strength of the coconut fiber composite material as a result of the press hand lay-up method with post-curing treatment on the variable duration of heat curing. With a duration of 60, 120, 180 minutes, heat curing will find out which variation has the best effectiveness, considering several factors to increase the strength of composite materials, one of which is heat curing treatment can make coconut fiber composites have higher tensile strength values and are able to utilizing coconut fiber waste which is more useful than usual as an embodiment of 3R (reuse, recycle, reduce.) through methods commonly used for composite manufacture in general and focusing on the percentage increase in post-curing results will be a reference and reference for further research to realize the creation of coconut fiber composite which is more useful. The process of making coconut fiber composites in this TA uses the press hand lay-up method, with alkalization soaking first and then post-curing treatment using an oven with a constant temperature of 100°C. To find the specifications and the percentage of this strength increase factor is by means of a tensile test with the parameters obtained: Ultimate Tensile Strength, strain, modulus of elasticity, and poisson ratio. With the highest result is at a duration of 3 hours worth 47.09 MPaKeywords: composite, Resin Polyester, coconut fiber, tensile test, heat curing, post-curing